Determinants of marriage dissolution in Seremban / Nornai’mah Mahadi, Nurul Huda Ahmad Jeffry and Umairah Mohd Zaini - Mahadi, Nornai’mah; Ahmad Jeffry, Nurul Huda; Mohd Zaini, Umairah (2019)
Every married couple surely will face the ups and clowns in maintaining the stability and lifelong of their marriage. One of the social problems that involve in a marriage life is known as divorce. Divorce is the legal dissolution of a marriage by a court or other competent body. In Seremban, there arc divorce cases which happen even after over 30 years of marriage. This issue is very worrisome because it not only can affect the couples involved, but also their family and children. Besides that, it can also threaten the social relations in our country. Thus, this study was conducted by using descriptive and logistic regression analysis with the aims to identify the trends of marriage dissolution as well as to examine the significant factors that cause high divorce rates in Seremban. In this study, the data consists of divorce cases in 20 I 7 which were collected from Jabatan Kehakiman Syariah Negeri Sembilan and it involved 430 couples where 312 of them were divorced while the remaining 118 were still married. Based on the logistic regression analysis, it can be summarized that only four out of l 2 independent variables were found to be statistically significant which are the husband's age, husband's income, irresponsible and spouses' attitudes. This study would not only be a benefit to all of the married couples, but also to the society, government and religious leaders in Malaysia.